2001
DOI: 10.2118/74141-pa
|View full text |Cite
|
Sign up to set email alerts
|

Unified Model for Steady-State Foam Behavior at High and Low Foam Qualities

Abstract: Summary Foams are routinely used worldwide to divert acid in well-stimulation treatments, and to divert gas flow in improved oil recovery (IOR) projects on a pilot basis. The complexity of foam behavior and the apparent contradictions among foam studies have bedeviled attempts to understand foams and to design effective field treatments. In 1992, Osterloh and Jante1 identified two distinct foam-flow regimes: a high-quality (dry) regime, in which the steady-state pressure gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
104
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(118 citation statements)
references
References 30 publications
11
104
2
Order By: Relevance
“…In the low-quality regime, bubble size thought to be unchanging and pressure gradient depends on porous medium and to lesser extent on surface tension, but not on ability of surfactant to stabilize foam (Rossen & Wang 1999). The transition between regimes is sensitive to both the nature of the porous medium and ability of surfactant to stabilize foam (Alvarez et al, 2001). In our model fracture, we observe different phenomena that contribute to the existence of the two flow regimes.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In the low-quality regime, bubble size thought to be unchanging and pressure gradient depends on porous medium and to lesser extent on surface tension, but not on ability of surfactant to stabilize foam (Rossen & Wang 1999). The transition between regimes is sensitive to both the nature of the porous medium and ability of surfactant to stabilize foam (Alvarez et al, 2001). In our model fracture, we observe different phenomena that contribute to the existence of the two flow regimes.…”
Section: Resultsmentioning
confidence: 75%
“…16,17,and 18). It is thought that average bubble size is unchanging in the lowquality foam regime in 3D porous media (Alvarez et al, 2001;Rossen & Wang 1999). Bubbles are thought to be as large as pores in that regime.…”
Section: Resultsmentioning
confidence: 99%
“…Foam is not a separate phase but a mixture of separate phases, gas and water, with peculiar rheology in the presence of surfactant. To a reasonable approximation, the total mobility of steady-state foam in porous media can be approximated as a power-law fluid at fixed quality (fixed gas fractional flow) over a limited range of superficial velocity (Alvarez et al 2001;Mamun et al 2002;Rong 2002;Kim et al 2005). The "low-quality regime" (flow at relatively low water fractional flow) in particular is strongly shear-thinning.…”
Section: Region Of Increased Permeability Near the Wellmentioning
confidence: 99%
“…[30] In this model, pressure gradient (rp) was defined as the ratio between pressure drop and the length of core. The strength of foams could also be measured by rp.…”
Section: Dynamic Stability Of Compressed Foam In Porous Mediamentioning
confidence: 99%
“…The strength of foams could also be measured by rp. Previous studies [30][31][32] identified two distinct strong foam-flow regimes. A high-quality (dry) regime (vertical contours in Figure 7), in which the steady-state rp is independent of the gas flow rate (U g ).…”
Section: Dynamic Stability Of Compressed Foam In Porous Mediamentioning
confidence: 99%